2022
DOI: 10.3390/nu14153057
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Milk-Derived Extracellular Vesicles on the Colonic Transcriptome and Proteome in Murine Model

Abstract: Evidence shows that effective nutritional intervention can prevent or mitigate the risk and morbidity of inflammatory bowel disease (IBD). Bovine milk extracellular vesicles (mEVs), a major bioactive constituent of milk, play an important role in maintaining intestinal health. The aims of this study were to assess the effects of mEV pre-supplementation on the colonic transcriptome and proteome in dextran sulphate sodium (DSS)-induced acute colitis, in order to understand the underlying molecular mechanisms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…1B) in DSS-induced colitis. 21 Histological analysis found that mEVs significantly decreased the infiltration of inflammatory cells, mucosal injury, and overall histology score 21 (Fig. 1C and D).…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…1B) in DSS-induced colitis. 21 Histological analysis found that mEVs significantly decreased the infiltration of inflammatory cells, mucosal injury, and overall histology score 21 (Fig. 1C and D).…”
Section: Resultsmentioning
confidence: 93%
“…Isolation of bovine mEVs was carried out as previously described. 21 All centrifugation was performed at 4 °C. Whole milk samples were centrifuged at 3000 g for 30 min and subsequently at 12 000 g for 60 min to remove fat globules, casein aggregates, and residual chymosin.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the EVs effectively upregulated the expression of anti-inflammatory genes and downregulated the expression of proinflammatory genes on a total of 1659 down-regulated and 1981 up-regulated genes, including 82 long noncoding RNAs and 6 circRNAs with regulatory functions 0/0/0000 0:00:00 AM. A similar transcriptome and proteome profiling analysis revealed a significantly reduced expression of proinflammatory cytokines (IL-1β, IL-6, IL-17A, and IL-33), chemokine ligands (CXCL1, CXCL2, CXCL3, CXCL5, CCL3, and CCL11), and chemokine receptors (CXCR2 and CCR3), as well as 109 upregulated and 150 downregulated proteins involved in modulating amino acid metabolism and lipid metabolism [ 170 ].…”
Section: Intrinsic Therapeutic Potential Of Mevsmentioning
confidence: 99%
“…The first challenge to overcome is the selection of appropriate animal models to achieve the desired goal. Vertebrate animal models have proven their efficacy in screening inflammatory responses and determining specific molecular therapeutic targets in human medicine ( 23 25 ). In this context, zebrafish (ZF) emerged as an outstanding genetically tractable and practical model for screening the biological process of inflammation in vivo ( 26 , 27 ).…”
Section: Introductionmentioning
confidence: 99%